Eliciting the Determinants of Management Specialization Course Selection: A Consumer Behaviour Perspective - Shrestha, Shankar Kumar; Shrestha, Bikash (PYC Nepal Journal of Management, 2020)
This study utilizes a survey of TU BBA students studying in 8th semester in an effort to understand how they choose their specialization courses by incorporating the attitude formation theory from a consumer behavior perspective. The study used multi stage sampling technique from 10 out of 25 TU BBA campuses. The sample size of the study is 114 students specializing the banking and finance, and sales and marketing in 8th semester. The sample size is sufficient at alpha level (0.05), power (0.8) and anticipated effect size of 0.1 for the hierarchical regression with two and three number of predictors in last two models of the study and for performing t test. The study demonstrated that the GPA in math and FPC underpin the course major decision of students vary significantly between finance and marketing specializing. The findings of this study indicate that students who choose banking and finance as a course major have higher confidence in their strength in mathematics. The study further concludes that students in choosing a higher education program give relatively great importance to various labor market aspects.